Digital design and time on device; how aesthetic experience can help to illuminate the psychological impact of living in a digital culture. Issue 3 (3rd July 2019) - Bartlett, Vanessa
ABSTRACT: Aesthetic techniques are increasingly used by marketeers to create enticing digital products. In this paper, I work with the aesthetic experiences of one audience group to consider the psychological impact of living in a culture where digital devices are deliberately designed to influence behaviour. I argue that aesthetic encounters can help with understanding the impact of the interplay between visual stimulus, affect and digital culture, in ways that may support situated understandings of mental distress in a digital age. I show how audiences respond to the artist-led research project Are We All Addicts Now? arguing that they generate ideas connected to submersion and being overwhelmed as a means of reporting on their own personal experiences of living in a digital culture that seeks to influence behaviour. The findings may have value for designers, curators and artists invested in understanding the experiential impact of digital devices.